Analisis Faktor - Faktor Yang Mempengaruhi Ekspor Karet Indonesia Ke Amerika Serikat - Kamalia Kamalia; Ali Wardhana (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2022)
This study aims to analyze the factors affecting the Indonesian rubber exports to the United States. The variables observed in this research were the value of Indonesian rubber exports to the United States, international rubber prices, the rupiah against the dollar exchange rate, US GDP per capita, and inflation. The data analysis technique used is Ordinary Least Square (OLS), with a period of time from 1995 to 2019. The result of the study shows that the variables of the dollar exchange rate against the rupiah, international rubber prices and GDP per capita in the United States have a joint effect. The exchange rate variable is the most dominant factor partially.